If f(x) = 2x – 6 and g(x) = 3x + 9, find (f+ g)(x).

Question

If f(x) = 2x – 6 and g(x) = 3x + 9, find (f+ g)(x).

in progress 0
Dulcie 7 months 2021-08-07T15:35:55+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-08-07T15:37:40+00:00

    Answer:

    (f + g)(x) = 5x + 3

    General Formulas and Concepts:

    Pre-Algebra

    Order of Operations: BPEMDAS

    1. Brackets
    2. Parenthesis
    3. Exponents
    4. Multiplication
    5. Division
    6. Addition
    7. Subtraction
    • Left to Right

    Algebra I

    • Terms/Coefficients
    • Functions
    • Function Notation

    Step-by-step explanation:

    Step 1: Define

    Identify

    f(x) = 2x – 6

    g(x) = 3x + 9

    (f + g)(x) is f(x) + g(x)

    Step 2: Find

    1. Substitute in function values:                                                                          (f + g)(x) = 2x – 6 + 3x + 9
    2. Combine like terms:                                                                                         (f + g)(x) = 5x + 3

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )